LCC-Demons: A robust and accurate symmetric diffeomorphic registration algorithm - Lorenzi, M.; Ayache, N.; Frisoni, G.B.; Pennec, X. (NeuroImage (Orlando, Fla.), 2013)
Non-linear registration is a key instrument for computational anatomy to study the morphology of organs and tissues. However, in order to be an effective instrument for the clinical practice, registration algorithms must be computationally efficient, accurate and most importantly robust to the multiple biases affecting medical images. In this work we propose a fast and robust registration framework based on the log-Demons diffeomorphic registration algorithm. The transformation is parameterized by stationary velocity fields (SVFs), and the similarity metric implements a symmetric local correlation coefficient (LCC). Moreover, we show how the SVF setting provides a stable and consistent numerical scheme for the computation of the Jacobian determinant and the flux of the deformation across the boundaries of a given region. Thus, it provides a robust evaluation of spatial changes. We tested the LCC-Demons in the inter-subject registration setting, by comparing with state-of-the-art registration algorithms on public available datasets, and in the intra-subject longitudinal registration problem, for the statistically powered measurements of the longitudinal atrophy in Alzheimer's disease. Experimental results show that LCC-Demons is a generic, flexible, efficient and robust algorithm for the accurate non-linear registration of images, which can find several applications in the field of medical imaging. Without any additional optimization, it solves equally well intra & inter-subject registration problems, and compares favorably to state-of-the-art methods. •LCC-Demons: logDemons-based robust diffeomorphic registration framework•The similarity metric implements the symmetric local correlation coefficient.•Stable numerical scheme for computing Jacobian determinant and flux of deformations•Inter-subject setting: LCC-Demons favorably compares to the state of the art methods.•Intra-subject setting: statistical powered measures of annual atrophy in Alzheimer's disease